1984
DOI: 10.1017/s0022172400064883
|View full text |Cite
|
Sign up to set email alerts
|

A bacteriocin produced by certain M-type 49Streptococcus pyogenesstrains when incubated anaerobically

Abstract: SummaryBacteriocin production (P)-typing of 75 M-type 49 group-A streptococci obtained from a variety of epidemiological incidents in different countries gave no evidence of production under the usual aerobic test conditions. However, with anaerobic incubation, 28% of the strains gave a pattern of inhibitory activity against the indicator strains which was indistinguishable from that previously attributed to the bacteriocin, streptococcin A-FF22 (SA-FF22). Isolation and partial purification of the M type 49 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Of the 21 strains tested, 7 strains (33%) produced an inhibitory activity, after anaerobic incubation, indistinguishable from that of strain FF22. In accordance with the results of a previous survey (15), none of the M-type 49 strains tested in the current study produced an ScnA-like inhibitory pattern following aerobic incubation. Strains were also examined by the PCR technique with crude cell lysates as previously described (4).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Of the 21 strains tested, 7 strains (33%) produced an inhibitory activity, after anaerobic incubation, indistinguishable from that of strain FF22. In accordance with the results of a previous survey (15), none of the M-type 49 strains tested in the current study produced an ScnA-like inhibitory pattern following aerobic incubation. Strains were also examined by the PCR technique with crude cell lysates as previously described (4).…”
supporting
confidence: 93%
“…Tagg and Skjold (15) previously reported that 28% (21 of 75) of Streptococcus pyogenes strains of M-type 49 tested produced an inhibitory activity indistinguishable from that attributed to ScnA. These strains were from different phage subtypes and were isolated from various geographical regions.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The production experiment was repeated without adjusting the pH of the medium after fermentation (without adsorption) to calculate levels of lantibiotics attached to the producer cells. However, attempts to recover lantibiotics from the cell-free supernatant of this preparation using 80% ammonium sulphate saturation as described previously [41] showed that 60–70% of lantibiotic produced by NU10, YU10 and K12 strains presented in this study is cell-wall associated peptide ( Table 7 ). The bacteriocin units (arbitrary units) were calculated as mentioned previously [38] .…”
Section: Resultsmentioning
confidence: 69%